Tracing global flows of bioactive compounds from farm to fork in nutrient balance sheets can help guide intervention towards healthier food supplies - Lividini, Keith; Masters, William A (Nature Publishing Group, 2022)
Adequate supplies of healthy foods available in each country are a necessary but not sufficient condition for adequate intake by each individual. Here we provide complete nutrient balance sheets that account for all plant-based and animal-sourced food flows from farm production through trade to non-food uses and waste in 173 countries from 1961 to 2018. We track 36 bioactive compounds in all farm commodities recorded by the Food and Agriculture Organization of the United Nations, accounting for nutrient-specific losses in processing and cooking as well as bioavailability. We compare supply with requirements given each country’s age–sex distribution and find that the adequacy of food supplies has increased but often remains below total needs, with even faster rise in energy levels and lower density of some nutrients per calorie. We use this nutrient accounting to show how gaps could be filled, either from food production and trade or from selected biofortification, fortification and supplementation scenarios for nutrients of concern such as vitamin A, iron and zinc.